1998
DOI: 10.1016/s0006-3495(98)77991-3
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of Dynamic Protein-DNA Interactions with a Dedicated Atomic Force Microscope

Abstract: Photolyase DNA interactions and the annealing of restriction fragment ends are directly visualized with the atomic force microscope (AFM). To be able to interact with proteins, DNA must be loosely bound to the surface. When MgCl2 is used to immobilize DNA to mica, DNA is attached to the surface at distinct sites. The pieces of DNA in between are free to move over the surface and are available for protein interaction. After implementation of a number of instrumental improvements, the molecules can be visualized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
96
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 29 publications
5
96
2
Order By: Relevance
“…By fixing DNA on a mica surface, the random displacements due to sliding of Aspergillus nidulans photolyase have been directly detected (13). The drawback of this method is slowing down of the movements of molecules because of interaction with a surface.…”
Section: Practical Definitions Of Translocation Mechanismsmentioning
confidence: 99%
“…By fixing DNA on a mica surface, the random displacements due to sliding of Aspergillus nidulans photolyase have been directly detected (13). The drawback of this method is slowing down of the movements of molecules because of interaction with a surface.…”
Section: Practical Definitions Of Translocation Mechanismsmentioning
confidence: 99%
“…This technology not only enables the confirmation of established hypotheses in biology, such as the hand-over-hand motion of myosin [6], but also has the potential to further the understanding of how protein complexes and nucleic acids interact, something that is critical to all forms of life [7][8][9][10][11][12][13]. HS-AFM can also be applied in the study of a wide range of biologically inspired materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, this point has been challenged [18] and it has even been suggested that the real structure of PHF could be a hybrid of the two, the paired helical filament model and that of the thin helical ribbon model [34]. AFM is a very adequate technique to observe biomolecules and other molecular assemblies [27,28,43]. From the structural point of view, the technique can image structures in native conditions, in three dimensions without staining or shadowing, in air or under liquid conditions (see for reviews [5,8,40]).…”
Section: Introductionmentioning
confidence: 99%